2018
DOI: 10.1111/echo.13894
|View full text |Cite
|
Sign up to set email alerts
|

Global and regional left ventricular circumferential strain during incremental cycling and isometric knee extension exercise

Abstract: Global circumferential strain increased stepwise during incremental cycling, mediated by the apex with trivial changes at the base. In contrast, GCS decreased during the isometric knee extension to 40% MVC and then plateaued, due to decreased BCS as ACS was maintained. A novel finding is that the GCS response appears to be exercise modality dependant and is the consequence of region-specific changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…During incremental dynamic aerobic exercise, studies reported a progressive increase in GCS due to increased apical circumferential strain (ACS) with trivial effects on basal circumferential strain (BCS). 26 In contrast, GCS decreased during the isometric exercise with no effect on ACS and decreased BCS from rest. 26 Therefore, exercise modality plays some role in GCS responses, and we did not have a granular breakdown of PA type.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…During incremental dynamic aerobic exercise, studies reported a progressive increase in GCS due to increased apical circumferential strain (ACS) with trivial effects on basal circumferential strain (BCS). 26 In contrast, GCS decreased during the isometric exercise with no effect on ACS and decreased BCS from rest. 26 Therefore, exercise modality plays some role in GCS responses, and we did not have a granular breakdown of PA type.…”
Section: Discussionmentioning
confidence: 91%
“…26 In contrast, GCS decreased during the isometric exercise with no effect on ACS and decreased BCS from rest. 26 Therefore, exercise modality plays some role in GCS responses, and we did not have a granular breakdown of PA type. Further studies of global and region-specific circumferential strain during incremental exercise are lacking at present, and GCS responses during dynamic and static modalities remain incompletely understood.…”
Section: Discussionmentioning
confidence: 91%